Identification of a New Antifungal Peptide W1 From a Marine Bacillus amyloliquefaciens Reveals Its Potential in Controlling Fungal Plant Diseases - Wen, Qiao; Liu, Ruizhe; Ouyang, Zhenxiao; He, Tianliang; Zhang, Weini; Chen, Xinhua (Frontiers in Microbiology, 2022)
A bacterium, Bacillus amyloliquefaciens W0101, isolated from the Arctic Ocean， showed potent antifungal activity against several plant pathogenic fungi. An antifungal peptide W1, with a molecular weight of approximately 2.4 kDa, was purified from the culture supernatant of the strain W0101 using ion-exchange chromatography and high-performance liquid chromatography. By analysis of LC-MS/MS, the peptide W1 was identified as a new antifungal peptide derived from the fragment of preprotein translocase subunit YajC. Further analysis revealed that W1 could disrupt the hyphae and spore of Sclerotinia sclerotiorum and inhibit its growth. W1 suppressed S. sclerotiorum and Fusarium oxysporum at a minimum inhibitory concentration of 140 and 58 μg/ml, respectively. The antifungal activity of W1 remained stable at 20-80℃ or pH 6-11, with reduced activity at 100-110°C and pH 4-5, and under three protease treatments. Additionally, W1 also had a certain extent of metal ion resistance. These results therefore suggested that the peptide W1 from marine B. amyloliquefaciens W0101 may represent a new antifungal peptide with potential application in the biocontrol of plant diseases.